DEWAN KOMISARIS, KARAKTERISTIK PERUSAHAAN DAN RISK MANAGEMENT COMMITTEE (Students' Journal of Accounting and Banking, 2013)
This study aims to examine the impact of board commissioner and firm characteristics to the existence of Risk Management Committee (RMC) in manufacturer firms. Existence RMC is reffered to this study is the disclosure of the exiztence of RMC, whether it is combined or separated from audit committee. Board characteristics variables used in the study are INDCOM, board size, independent audit committee, and meeting frequency of board commissoner. While the firm characteristics are represented by firm size and financial reporting risk. Data was collected by using a purposive sampling method toward  manufacturer firms listed on the Indonesia Stock Exchange in 2009 until 2011. Total of 189 manufacturer firms to be sampled in this research. Statistical method that used to test the hypothesis is logistic regression analysis. The result of this study showed that all of independent variable that has not affect significantly the existence of RMC. While the variables that affect significantly the existence of Separate RMC (SRMC) from audit committee are independency of audit committee, meeting frequency of board commissioner and firm size. Keywords: Risk Management Committee, Separate Risk Management Committee, Board of Commissioner Characteristics, and Firm Characteristics.